Daya Tarik Perubahan Taman R.A Kartini Cimahi Sebagai Alternatif Berwisata - Geliya Cerita Kusuma; Heni Novia Fitri (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2024)
This research aims to introduce the tourist attractions and attractiveness of Kartini Park in Cimahi, West Java. This park can be used as an alternative place to travel for the surrounding community at an affordable price with various facilities, a clean and cool place, so it can be a special attraction value. The problems found in the area are: 1) The history of Kartini Park; 2) The initial negative perspective of the community towards Kartini Park; 3) The reason why Kartini Park is an attraction for local tourists in Cimahi city. The method used is observation in digital research. The results of this research will show that the management of Kartini Park is quite good and maintained. In addition, this research can be an alternative for families and relatives as well as the closest people to travel to spend holidays together.